A Study of the Feasibility of Pinus patula Biochar: The Regeneration of the Indigo Carmine-Loaded Biochar and Its Efficiency for Real Textile Wastewater Treatment (2024)
ABSTRACT: The feasibility of an adsorbent material like biochar (BC) depends on its regeneration capacity and its ability to achieve high removal efficiencies on real wastewater (WW) effluents. In this study, the regeneration capacity of the Pinus patula BC previously used in the removal of Indigo Carmine from water was evaluated. The regeneration technique that resulted in the highest desorption efficiency was a thermo-chemical method that consisted of heating the spent BC in a stove at 160 ◦C for 45 min followed by regeneration with ethanol (C2H6O) at a concentration of 75% for 6 h. Through this regeneration method, it was found that Pinus patula BC could be used in seven consecutive adsorption–desorption cycles. The feasibility of this BC was also assessed by evaluating the adsorbent’s efficiency in real textile WW. Under optimal operational conditions (solution pH = 3, BC dose = 13.5 g/L, and BC particle size = 300–450 μm), the highest removal efficiencies in terms of colour and dissolved organic carbon (DOC) were 81.3 and 76.8%, respectively, for 120 min of treatment. The results obtained in the regeneration studies and the treatment of real textile WW suggested that the use of Pinus patula BC could be suitable to be scaled to an industrial level, contributing to sustainable development and the circular bioeconomy by using a waste to solve the dye pollution problem of another waste.